"Adventure of Democracy" Seen Through Animal Metaphors Created By 6th Grade Students. (2nd June 2015) - Selcuk, Gulenaz; Altintas, Gulşen; Ciritci, Hacı Mustafa
Abstract: A group of 41 students in a 6 th grade class of 75. Yıl Secondary School in the province of Demirci in Manisa, Turkey, are asked to create animal metaphors about perception, constitutionalism, secularism, monarchy, oligarchy, freedom and executive for the unit on democracy adventure, a subject discussed in Social Science class. The animals that the students have chosen for the representation are from different habitats but through the different techniques of analysis, it was seen that this choice is not arbitrary. The animal metaphors represent their mental images of the related concepts. At the same time, the animals used by the students are in connection with their own environment and also their knowledge about these animals and their characteristics.